High Proteoglycan Decorin Levels Are Associated With Acute Coronary Syndrome and Provoke an Imbalanced Inflammatory Response - Zhuang, Lingfang; Ge, Yulong; Zong, Xiao; Yang, Qian; Zhang, Ruiyan; Fan, Qin; Tao, Rong (Frontiers in Physiology, 2021)
Background and Aims: Acute coronary syndrome (ACS) has become one of the most common causes of disability. It is thus important to identify ACS early in the disease course of patients using novel biomarkers for prompt management. Decorin (DCN) was well-acknowledged for its effect on collagen fibrillogenesis and maintaining tissue integrity. Additionally, DCN could release as secreted proteoglycan under pathological conditions. Hence, we aimed to determine the relationship between serum DCN concentration and ACS. Methods: A total of 388 patients who underwent coronary angiography (CAG) in the cardiovascular center of Ruijin Hospital between June 2016 and December 2017 were enrolled in this study. Blood samples were drawn during CAG surgery to determine the serum DCN level of patients with ACS (n = 210) and control subjects (n = 178) using enzyme-linked immunosorbent assay. Results: We found that the serum DCN levels of ACS patients were elevated compared with those of the control subjects (13.59 ± 0.50 vs 13.17 ± 0.38, respectively, p < 0.001). Furthermore, the serum DCN level, after being adjusted with other cardiovascular factors, was independently associated with ACS. Moreover, an increased serum DCN level was positively correlated with the number of white blood cells and the level of high-sensitivity C-reactive protein (R = 0.3 and 0.11, respectively). Mechanistically, DCN might have elicited an imbalanced inflammatory response during cardiac ischemia by suppressing the expression of anti-inflammatory genes. Conclusion: Serum DCN is a novel biomarker of ACS and contributes to the increased inflammatory response in ischemic heart disease.